2014
DOI: 10.1063/1.4897001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and transport properties of epitaxial stepped Fe3O4(100) thin films

Abstract: We investigate the magnetic and transport properties of epitaxial stepped Fe3O4 thin films grown with different thicknesses. Magnetization measurements suggest that the steps induce additional anisotropy, which has an easy axis perpendicular to steps and the hard axis along the steps. Separate local transport measurements, with nano-gap contacts along a single step and perpendicular to a single step, suggest the formation of a high density of anti-phase boundaries (APBs) at the step edges are responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
4
10
0
Order By: Relevance
“…Therefore, high density APBs will be formed at the step edges [32][33][34] and the density of APBs at the step edges should be more than 50% higher than that on the terrace, which is consistent with our experimental observation, as the V ON SW for devices with four contacts in the AS configuration is almost 50% greater than for devices with four contacts in the PS configuration. Therefore, high density APBs will be formed at the step edges [32][33][34] and the density of APBs at the step edges should be more than 50% higher than that on the terrace, which is consistent with our experimental observation, as the V ON SW for devices with four contacts in the AS configuration is almost 50% greater than for devices with four contacts in the PS configuration.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, high density APBs will be formed at the step edges [32][33][34] and the density of APBs at the step edges should be more than 50% higher than that on the terrace, which is consistent with our experimental observation, as the V ON SW for devices with four contacts in the AS configuration is almost 50% greater than for devices with four contacts in the PS configuration. Therefore, high density APBs will be formed at the step edges [32][33][34] and the density of APBs at the step edges should be more than 50% higher than that on the terrace, which is consistent with our experimental observation, as the V ON SW for devices with four contacts in the AS configuration is almost 50% greater than for devices with four contacts in the PS configuration.…”
Section: Discussionsupporting
confidence: 89%
“…A voltage is applied to the source lead with the drain grounded, and the current passing through the channel is measured. 32 Here, to clearly distinguish the origin of the anisotropic switching, we measured the resistive switching behavior in Fe 3 O 4 films with large thicknesses where the APBs effect on the long-range charge-orbital ordering is weaker as the distance between APBs or APB domain size increases with increasing film thickness. 2a shows a scanning electron microscopy (SEM) image of a typical device with four probe contacts in a PS configuration, where the electrical field is applied along the steps.…”
Section: Rs In Magnetitementioning
confidence: 99%
See 1 more Smart Citation
“…Through detailed high resolution cross-sectional TEM investigations, we observed that the films possess the epitaxial relationship with the substrate and step-terrace periodicity propagated through the entire thickness [11,14]. Magnetization studies of Fe3O4 films on vicinal MgO revealed an in-plane uniaxial magnetic anisotropy induced by step-edges with an easy axis along the PSE direction for temperatures above the Verwey transition [19]. Whereas, for temperatures below the Verwey transition there was a transition of easy axis from PSE to SE, which was also found to be thickness dependent.…”
Section: Resultsmentioning
confidence: 95%
“…Prior annealing in a tube furnace, samples were treated in an ultrasonic bath using acetone, methanol, and high purity isopropanol. Further details on the dependence of the final template structure on annealing conditions has been previously published . The anneal conditions and properties of templates used in this study are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%